Evaluating the Effectiveness of Duralabhadi Kashaya in the Management of Urinary Tract Infections (International Journal of Ayurveda and Pharma Research, 2025)
Urinary tract infections are common bacterial infection affecting the urinary tract, with a higher prevalence in females. Urinary tract infections are defined as presence and multiplication of the bacteria. Around 50% of women will be treated for atleast one urinary tract infections during their lifetime. In Ayurveda, urinary tract infections can be correlated to Pittaja Mutrakrichra in which Vata and Pitta Dosha are vitiated. So drugs with Pittavatahara, Sothahara, Krimighna, Mutrala, and Vatanulomana are beneficial. So Duralabhadi Kashaya with Sitha as Anupana mentioned in Gada Nigraha, Mutrakrichra Prakaranam having above mentioned property was selected as trial drug. The present study aims to evaluate the effectiveness of Duralabhadi Kashaya in the management of urinary tract infection. Subjects of all gender from 20-60, satisfying the inclusion criteria were subjected to positive sampling and total of 26 subjects were selected for the study. The selected subjects were given Duralabhadi Kashaya Choorna packet 48gm per day, advised to take freshly prepared Kashaya 48ml along with Sitha 6gm as Anupana twice daily before food for 15 days and follow up was done after 15 days of treatment. Assessment of the subjects was done on 0th day, 6th day, 11th day, 16th day and follow up on 31st day with subjective and objective parameters. Based on the observations and results it has been found that subjective parameters and objective parameters got statistically significant result.